Nazwy nieoficjalne żeńskich zgromadzeń zakonnych i ich członkiń w Polsce - Warzecha, Beata (Słowo. Studia językoznawcze, 2014)
The subject of my article is the analysis of the 106 unofficial two components or several ones of the colloquial names of the women’s religious congregations and their members in Poland. These words are known to the ‘ordinary’ people and they are used to identify the given congregation. The common names are often the shorts of the full official names. The analysis shows the mechanism how to create the colloquial names in their relation to the full official names. It indicates the characteristic nomination models, it also draws the attention to the diversity of lexical bases and how to create a subordinate member. The characteristics of these names is shown from the point of view of the main body. Within the established groups names were downgraded due to the defining members expressed as: the attributive adjective, the attributive genitive, the attributive prepositional and the attributive nouns. The specifying part of these colloquial names is not various and it can come from the name or the surname of the congregation’s founder, the name of the patron or the patron’s attribute, the name of the registered office, the business’s place or the establishing of the congragation, the word defining the field of activity, the word indicating the colour of the outfit.